POLITICISATION OF CEO APPOINTMENT IN LITHUANIAN STATE-OWNED ENTERPRISES - Laurišonytė, Neringa (Politologija, 2014)
This article analyses the turnover and politicisation of CEO positions in Lithuanian state-owned enterprises (SOEs). Since SOEs operate in many strategically important sectors, the politicisation of CEO positions is seen as a particularly harmful practice. Thus, the main aim of the article is not only to identify the scope of politicisation and changes in CEO positions, but also to account for variation in the extent of politicisation in terms of different legal statuses of these enterprises, policy fields, types of government, party entrenchment and membership. The results aggregate data on 153 SOEs and 369 CEOs between 1990 and 2012. First, the data confirmed that larger political parties with a longer experience in office appointed most of the politicised CEOs. These results are in line with the findings of previous research that politicisation increases along with the years a party spends in power. They also confirm a theoretical assumption about the impact of party entrenchment on the size of party networks and the ability of political parties to place loyalists in public sector organisations. Second, the results of this article revealed that CEO turnover is best explained by the factors of changing ruling majorities and governments. The fact that after a major change in the ruling majority CEO redundancies increase almost three times explains why more than a half of the CEOs appointed by majority coalition governments do not stay in office longer than three years. However, it is important to note that almost half of all the CEOs were made redundant by the 2008–2012 Lithuanian Government, which came into power after a major change as a majority coalition. Therefore, it can be concluded that the above mentioned results are determined primarily by policies of this particular Government. On the other hand, neither a ruling majority change nor a government type explains politicisation. In order to understand this phenomenon, it is essential to distinguish among policy fields. Sectoral analysis showed that energy and forestry are the most politicised sectors. However, the time that CEOs from the energy enterprises spend in office is about four times shorter compared to CEOs from the forestry sector and depends on the governing period of a particular party. This analysis leads to the conclusion that the situation in the energy sector is broadly in line with previous research findings about the outcomes of party competition when a winning party tries to strengthen its political authority by filling up the positions of public sector organisations with party loyalists. On the other hand, analysis of the forestry sector shows that CEOs themselves might be seeking party affiliation in order to gain a subsequent term in office. This conclusion points to different patterns of politicisation in different sectors of the economy. Therefore, it would be useful to not only carry out case studies of Lithuanian SOEs, but also to compare Lithuanian SOEs with other public sector organisations in Lithuania and abroad.